2002
DOI: 10.1128/jvi.76.11.5598-5604.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Acidic Activation Domain of the Baculovirus Transactivator IE1 Contains a Virus-Specific Domain Essential for DNA Replication

Abstract: IE1 is a potent transcriptional transactivator of the baculovirus Orgyia pseudotsugata multiple nucleopolyhedrovirus (OpMNPV) and has been shown to be essential for viral DNA replication. IE1 contains an acidic activation domain (AAD) at the N terminus that is essential for transcriptional transactivation, but its role in viral DNA replication is unknown. In this study the role of the IE1 AAD in DNA replication is investigated. We have determined that deletion of the AAD eliminates the ability of IE1 to suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…Our on May 10, 2018 by guest http://jvi.asm.org/ data support a model in which basic domain I functions to concentrate IE1 at the hr enhancers to stimulate transcription by a DNA-binding-dependent mechanism. By virtue of its hrbinding function, we predict that basic domain I is also required for IE1's role in DNA replication (17,35,40). Participation of basic domain I in hr enhancer binding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our on May 10, 2018 by guest http://jvi.asm.org/ data support a model in which basic domain I functions to concentrate IE1 at the hr enhancers to stimulate transcription by a DNA-binding-dependent mechanism. By virtue of its hrbinding function, we predict that basic domain I is also required for IE1's role in DNA replication (17,35,40). Participation of basic domain I in hr enhancer binding.…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type and mutated IE1s were synthesized for 2 h at 30°C by using 30-l coupled in vitro transcriptiontranslation reaction mixtures (TNT system; Promega) programmed with plasmid DNA and SP6 RNA polymerase. 35 S-labeled methionine-cysteine (NEN) was included only when levels of in vitro-synthesized protein were quantified by denaturing SDS-10% polyacrylamide gel electrophoresis. A 61-bp DNA probe containing the leftmost hr5 28-mer was generated by FokI and HinfI digestion of a PCR-derived fragment from plasmid phr5.1 (43).…”
Section: Plasmids (I) Ie1 Substitutions and Deletions Pie1mentioning
confidence: 99%
See 1 more Smart Citation
“…Forsythe et al (1998) performed a mutational analysis of OpMNPV IE1 AAD and showed that it comprised two activation subdomains. More recently, Pathakamuri & Theilmann (2002) showed that the AAD of OpMNPV IE1 also contains an essential DNA replication subdomain that is separate from the transcriptional activation domain.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of the alphabaculovirus Orgyia pseudotsugata MNPV (OpMNPV) revealed that the N-terminal 65 residues of OpMNPV IE1 are required for plasmid DNA replication assays in transfected cells (32). However, this N-terminal region and the complete transactivation domain of OpMNPV IE1 exhibit little if any sequence identity with AcMNPV IE1.…”
mentioning
confidence: 92%